Interfacial coupling heterostructure between transition metal oxide and calcium oxide with excellent sunlight-driven photocatalytic activity - Thanit Tangcharoen (Results in Surfaces and Interfaces)
The pollutants rhodamine B (RhB), methylene blue (MB), methyl orange (MO), and methyl red (MR) are highly toxic, and as a consequence their bioaccumulation is a problem which must be addressed through effective removal approaches. As contaminants, these azoic, phenol, and heteropolyaromatic dyes have genotoxic properties and present a long-lasting threat to human health. This study seeks to explore the potential for removing these dyes from wastewater through a photocatalytic technique making use of nanophotocatalysts which are based on calcium oxide and require synthesis using the sol-gel auto combustion method. Various metals are added to the calcium oxide powder (nickel (Ni), copper (Cu), and zinc (Zn)) and the effects of these additives upon the structures, chemical bonds, morphologies, specific surface area, chemical composition, optical, and magnetic properties, including photocatalytic capabilities were examined via the use of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), Brunauer-Emmett-Teller (BET) analysis, UV–visible diffuse reflectance spectroscopy (UV-DRS), vibrating sample magnetometry (VSM), and the analysis of photodegradation. The findings obtained via XRD and FT-IR confirmed that the composites of NiCaO, CuCaO, and ZnCaO offered very good purity and crystallinity, while the absorption levels were demonstrated by UV-DRS analysis to be significantly improved for those samples which had undergone modification in comparison to the pure sample when examined via the ultraviolet, visible, and infrared spectra. Analysis of VSM indicated that the samples which had been modified were capable of mixed magnetization behavior in which a higher magnetic field causes the diamagnetic signal to dominate the ferromagnetic signal. In contrast to the results with the pure samples, the degradation takes place much more rapidly for RhB (97%), MB (95%), MO (94%), and MR (93%) when the metal additives are optimized. These photocatalysts present a narrowed band gap and enhanced ratio of surface to volume, and these factors, along with the heterostructure formation of the modified photocatalysts can lead to better photocatalytic performance. It was revealed via scavenger analysis that the presence of superoxide free radicals is vital to convert these toxic pollutants into harmless by-products. Furthermore, once optimized, these catalysts are remarkably sustainable and inexpensive, and can be used for as many as four cycles before beginning to decline in terms of efficacy.